The Influence of Peer Education on The Change of Knowledge and Attitudes in The Prevention of HIV/AIDS in Fruit Vessel in Batu Ampar Port Area - Mira Agusthia; Winda Ramadhana (Universitas Muhammadiyah Mataram, 2019)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, especially all cells that have CD4 + markers on their surface such as macrophages and T lymphocytes, HIV infection can cause Acquired Immunodeficiency Syndrome (AIDS) which is characterized by gradual damage to immunity. AIDS affects immunity and even the autoimmunity. Kepulauan Riau health office notes Batam city is the highest case with 758 case HIV and 712 case AIDS. The result of mobile VCT service In BatuAmpar Health Quarantine at 2017 Showed from 2639 test of the high risk group (crewman, port warker, drivers ) 9 crewman infection HIV. The Purpose of This Studywas to determine the effect of giving peer education to change knowledge and attidues of crewman about prevention of HIV/AIDS in BatuAmpar International Cargo Port. This study was conducted on January 15, 2019. This study used a quasi-experimental method with the design of one group pretest-posttest design. The sample for this study used a purposive sampling method with a total sample of 20 respondents. The intervention that was carried out was the crew man which as the peer educator provided education about HIV/AIDS 3 times a week for 2 weeks in other crew man. Data were analyzed by paired T-tests (t-tests) which were previously tested for the Shapiro Wilk Normality Test. The results showed that there was an effect of peer education on changes in knowledge and attitudes in crew man in the prevention of HIV/AIDS in BatuAmpar port which was significant with a p-value of 0,000 (p <0.05). This study leads to the conclusion that there is an effect of peer education on changes in knowledge and attitudes in crew man in the prevention of HIV/AIDS. It is expected that the implementation of the peer education HIV/AIDS intervention will be increased at BatuAmpar port so that the crew man will know information about HIV/AIDS